Analisis Semiotika Roland Barthes Pada Iklan Aqua Versi “Aqua 100% Murni, 100% Indonesia - Febriana, Elisa; Nursanti, Siti; Hariyanto, Fajar (Jurnal Ilmiah Wahana Pendidikan, 2025)
Advertisement is an important element in the world of marketing that has a strategic role in influencing consumer behavior and creating awareness of a product. Advertisements not only play a role as a means of promotion, but also as a medium to influence consumer behavior and create an image of a product. Early in 2024, one of the largest mineral water products in Indonesia released its latest advertisement with the tagline "AQUA 100% MURNI, 100% INDONESIA". This latest version of the Aqua advertisement has its own uniqueness, namely by featuring an advertising star who is not like the usual advertisement featuring a famous public figure, but Aqua features one of its employees, this makes the current version of the Aqua advertisement interesting because it is different from previous Aqua advertisements. This study aims to analyze the meaning of denotation, connotation, and myth contained in this latest version of the Aqua advertisement. This study uses a qualitative research method with Roland Barthes' semiotic analysis technique.